Tindak Pidana Pelanggaran Kekarantinaan Kesehatan yang Mengakibatkan Kedaruratan Masyarakat - Ida Ayu Sri Wahyuni; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2022)
Regulations that have been regulated by laws and regulations, namely the Health Quarantine have a solution to limit community activities in breaking the chain of the COVID-19 pandemic. This study aims to analyze the handling of criminal acts of violation of the Covid-19 health quarantine and discuss criminal legal sanctions in the event of a health quarantine violation. This research is part of normative legal research, research by collecting legal materials in the form of primary, secondary and tertiary legal materials using a library approach. The results of the study explain that Government Regulation in Lieu of Law (Perpu) Number 1 of 2020 concerning Financial Policy and Financial System Stability for Handling the Covid-19 Pandemic and/or in order to deal with threats that endanger the National economy and/or Financial System Stability, hereinafter referred to as Perppu No.1/2020). Criminal sanctions for violating health quarantine are regulated in Article 93 of Law no. 6 of 2018 concerning Health Quarantine, which regulates parties who violate Article 9 paragraph (1) are threatened with a maximum fine of 100 million